I-Spring Suite as an Alternative Media for Algebraic Expression - Safira, Fatimah Gita; Priwantoro, Soffi Widyanesti; Nur Hidayah; Syariful Fahmi (Program Studi Matematika Fakultas Sains dan Teknologi UIN Sunan Kalijaga Yogyakarta, 2023)
A The limitation of technology-based learning media available at SMP Muhammdiyah 1 Godean motivate researcher to develop learning media that can supplement alternative media and also assist the difficulty faced by the students, especially in algebraic expression material. This research uses the Analysis, Design, development, Implemnetation and Evaluation (ADDIE) model. The subjects of this research is students of VII grade of SMP Muhammdiyah 1 Godean. Before being trialled into small and large classes, learning media will be validated by material and media experts. The result of the research obtained that the assessment of the material expert obtained 84% and from media expert get 95% with the predicate very feasible. Meanwhile the result of smaal and large trials obtained 83% and 82% who said the mdia was very feasible. So from these result it can be concluded that th learning media developed by researchers are feasible for use.